Effects of different cooking and drying methods on phenolic acids, carotenoids, and antioxidant activity of emmer (Triticum turgidum ssp. dicoccum) bulgur. Issue 6 (4th October 2019) - Yilmaz, Volkan Arif
Abstract: Background and objectives: Emmer ( Triticum turgidum ssp. dicoccum ) is an ancient hulled wheat with a high amount of nutrient and bioactive compounds. This study was aimed to investigate the changes in bioactive compounds and antioxidant activities of the emmer bulgurs produced by combinations of three cooking (traditional, autoclave, and microwave) and two drying (hot air and microwave) methods. The total polyphenol, carotenoid, antioxidant activity (DPPH radical scavenging activity and ferric reducing antioxidant power), and soluble‐free (SF), soluble‐conjugated (SC) and insoluble‐bound (IB) phenolic acid contents were determined. Findings: Bioactive compounds and antioxidant activity decreased significantly in all bulgur production methods compared to emmer wheat. SF and SC phenolic acids of the bulgur samples decreased much more than IB phenolic acids, due to the better thermal stability of IB fraction. While microwave cooking was found to have a positive effect, microwave drying had a negative effect on preserving natural bioactive compounds. Conclusions: The bulgur preparation method that most preserved the bioactive compounds was microwave cooking + hot air drying, followed by autoclave cooking + hot air. Significance and novelty: As a primitive species, emmer is a valuable raw material with a growing interest in its properties and products. This is the first study aimed to compare the effects of several production methods on the bioactive compounds and antioxidant activity of emmer bulgur.